Tingkat Pengetahuan Perekam Medis tentang Riwayat Medis dan Catatan Kesehatan Pribadi (PHR) - Masyfufah, Lilis Masyfufah; Prihandini, Retnowati Prihandini; Nudji, Bambang Nudji; Wahyuni, Titin Wahyuni (Jurnal Manajemen Kesehatan Yayasan RS.Dr. Soetomo, 2025)
A medical resume is a summary of the entire course of a patient's treatment at a healthcare facility, so the medical resume must be complete and valid. The existence of this medical resume is very important for patients because through the medical resume, patients can learn about their health history, especially if they use social health insurance. One of the expanded functions of the medical resume is in the form of a Personal Health Record (PHR) which contains a collection of records/information about an individual's health. The purpose of this study is to analyze the level of knowledge of medical recorders regarding medical resumes and PHR. This research is descriptive in nature, objectively describing a situation using a quantitative approach. The sample in this study uses non-probability sampling with a controlled pruposive sampling method. The results of the study showed that the level of knowledge of medical recorders about medical resumes and PHR was at the level of Application with scores of 43.3% and 33.3%. Medical recorders have been able to implement filling medical resumes and carry out PHR in activities in the field of medical records and health information. The level of knowledge of PMIK about medical resumes and PHR is at the level of application with the characteristics of male gender, aged 17-25 years, and working in private hospitals. Further knowledge improvement is needed so that medical recorders are more competent in implementing PHR.